Comparative Studies Between Indonesia and Philippines Conditional Cash Transfer Policy: an Integrative Literature Review - Astrid Fernanda; Wimmy Haliim (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2026)
Conditional cash transfer (CCT) interventions are prominent poverty-reduction instruments in Southeast Asia, yet systematic knowledge of the mismatch between design and reality remains insufficient. This integrative literature review analyzes 90 peer-reviewed articles comparing the Program Keluarga Harapan (PKH) in Indonesia and the Pantawid Pamilyang Pilipino Program (4Ps) in the Philippines. Based on a design-meets-reality model, the review studies consistency between design assumptions, implementation capacity, and contextual conditions. Findings indicate a systematic design-reality gap due to three theoretical shortcomings: transfer adequacy assumptions, complementarity assumptions, and a lack of behavioral change assumptions, which poorly address the beneficiary agency's multi-sectoral integration demands. The two programs operate under different institutional structures, which creates heterogeneity in implementation. Results show that CCT's effectiveness is mostly mediated contingently rather than deterministically by indices of implementation fidelity, supply factors, and situational conditions such as geographic marginality, disaster shocks, and conflict zones. Policy solutions to PKH involve realigning transfer adequacy, integrating complementary services, and reforming coordination, whereas 4Ps priorities involve lessening fragmentation, integrating health and nutrition, and enhancing transparency for recipients.